Use of reconstituted waters to evaluate effects of elevated major ions associated with mountaintop coal mining on freshwater invertebrates. (29th October 2013) - Kunz, James L.; Conley, Justin M.; Buchwalter, David B.; Norberg‐King, Teresa J.; Kemble, Nile E.; Wang, Ning; Ingersoll, Christopher G.
Abstract In previous laboratory chronic 7‐d toxicity tests conducted with the cladoceran Ceriodaphnia dubia, surface waters collected from Appalachian sites impacted by coal mining have shown toxic effects associated with elevated total dissolved solids (TDS). The objective of the present study was to evaluate the effects of elevated major ions in chronic laboratory tests with C. dubia (7‐d exposure), a unionid mussel (Lampsilis siliquoidea; 28‐d exposure), an amphipod (Hyalella azteca; 28‐d exposure), and a mayfly (Centroptilum triangulifer; 35‐d exposure) in 3 reconstituted waters designed to be representative of 3 Appalachian sites impacted by coal mining. Two of the reconstituted waters had ionic compositions representative of alkaline mine drainage associated with mountaintop removal and valley fill‐impacted streams (Winding Shoals and Boardtree, with elevated Mg, Ca, K, SO4, HCO3), and a third reconstituted water had an ionic composition representative of neutralized mine drainage (Upper Dempsey, with elevated Na, K, SO4, and HCO3). The waters with similar conductivities but, with different ionic compositions had different effects on the test organisms. The Winding Shoals and Boardtree reconstituted waters were consistently toxic to the mussel, the amphipod, and the mayfly. In contrast, the Upper Dempsey reconstituted water was toxic to the mussel, the amphipod, and the cladoceran but was not toxic to the mayfly. These results indicate that, although elevated TDS can be correlated with toxicity, the specific major ion composition of the water is important. Moreover, the choice of test organism is critical, particularly if a test species is to be used as a surrogate for a range of faunal groups. Environ Toxicol Chem 2013;32:2826–2835. © 2013 SETAC